Health Community Agents: attributions on children´s health - Fabíola Santos Bittencourt; Paula Lenhart Pereira; Susana Maria Gonzaga; Astrid Eggert Boehs; Ivonete Schulter Buss Heidemann; Ana Cristina Magalhães Fernandes Báfica (Universidade Federal de Santa Maria, 2011)
It is a descriptive, exploratory and qualitative research aimed to provide attributions from the Community Health Agents in families with children between zero and six years old that are tied to a Family Health Strategy team, in order to identify facilities, difficulties and doubts on that implementation. The place was an area attached to a basic health unit, using observation techniques at home visits, individual interview and workshops with a total of 15 agents. Categorized data were discussed in light of the Nursing Transcultural Theory and other authors. It has emerged the following categories: planning and collecting data at home visits, facilities, difficulties and doubts at home visits. It is concluded that, by giving voice to the, there are possibilities of exchanging experiences and knowledge between the popular and the professional care system